Achieving real business outcomes from artificial intelligence : enterprise considerations for AI initiatives - Kureishy, Atif; Meley, Chad; Mackenzie, Ben (O'Reilly Media, 2018)
Artificial intelligence is already changing industry landscapes, with early adopters reporting benefits in high-value business cases such as fraud detection, preventative maintenance, and recommendation engines. Yet working on an AI initiative is demanding for many enterprises, whether you're in the middle of the process or just getting started. This ebook provides advice to help your company complete your AI journey. Chad Meley from Teradata and Atif Kureishy and Ben Mackenzie from Think Big Analytics provide countermeasures for common AI challenges that arise when creating a strategy, dealing with technical issues, or operationalizing an AI initiative. You'll explore several case studies, including how a major bank successfully used a variety of deep learning methods to fight financial crime. With this ebook, you'll discover: How deep learning has the potential to increase production, drive down cost, reduce waste, improve efficiency, and push innovation Options and trade-offs for leveraging AI capabilities, including SaaS solutions, public cloud-based APIs, and custom AI models AI case studies for mining image data, using image recognition, providing customer service, and designing document automation How to overcome challenges in delivering value from custom AI development What to do in the face of emerging AI trends over the next three years.